Signs of Light in the Qur’an: Interpreting Symbolism through Peircean Semiotics - Hamid, Mas'an; Murtadho, Muhammad Alfa Choirul (Civiliza Publishing, 2024)
This study examines the Qur’anic symbolism of light through the semiotic framework of Charles S. Peirce. In the Qur’an, light (nūr) is frequently employed as a symbol that embodies divine guidance, spiritual enlightenment, and the manifestation of Allah’s presence. Peirce’s semiotic theory, with its triadic model, representamen (the sign), object (the referent), and interpretant (the meaning constructed by the observer), is applied to uncover the layered meanings of light in selected Qur’anic verses. This research analyzes and interprets verses that explicitly mention light in order to reveal both the apparent and hidden dimensions of its symbolism and its role in shaping the Qur’an’s overall message. Focusing particularly on QS. An-Nur: 35 (light as divine guidance), QS. Al-Baqarah: 257 (light as liberation from darkness), and QS. Al-Hadid: 12–13 (light as a reward in the hereafter), the study demonstrates how the Qur’an employs this symbol to communicate theological, spiritual, and ethical values. The findings aim to contribute to Qur’anic studies by enriching the understanding of symbolism in sacred texts and by illustrating the applicability of Peirce’s semiotic theory to the interpretation of religious discourse.